HH1-1, a novel Galectin-3 inhibitor, exerts anti-pancreatic cancer activity by blocking Galectin-3/EGFR/AKT/FOXO3 signaling pathway. (15th January 2019) - Yao, Yanli; Zhou, Lishuang; Liao, Wenfeng; Chen, Huanjun; Du, Zhenyun; Shao, Chenghao; Wang, Peipei; Ding, Kan
Highlights: An arabinogalactan HH1-1 derived from safflower has anti-pancreatic cancer activity. HH1-1 could bind to Galectin-3 and inhibit Galectin-3 expression. HH1-1 reduced the interaction between Galectin-3 and EGFR for 245.28 folds. HH1-1 influenced cancer cell proliferation, cell cycle, apoptosis, angiogenesis, migration and invasion. HH1-1 affected the Galectin-3/EGFR/AKT/FOXO3 signaling pathway in vitro and in vivo. Abstract: Pancreatic ductal adenocarcinoma is a highly malignant gastrointestinal tumor. Molecular targeting therapy for pancreatic cancer is still limited. High expressed Galectin-3 in pancreatic cancer is positively correlated with disease progression, indicating that Galectin-3 can be employed as a predictor of poor prognosis. From safflower, we isolated and purified a homogeneous polysaccharide, HH1-1, which could bind to and inhibit Galectin-3. HH1-1 could block the interaction between Galectin-3 and EGFR. Following HH1-1 treatment, the binding ability between EGFR and Galectin-3 was reduced by 245.28 folds. HH1-1 could suppress pancreatic cancer cell proliferation, arrest the cell cycle in S phase, induce cell apoptosis, inhibit angiogenesis and impede tumor cell migration and invasion. Moreover, HH1-1 affected the Galectin-3/EGFR/AKT/FOXO3 signaling pathway and possessed anti-pancreatic cancer activity in vitro and in vivo, especially in patient-derived xenografts. Further study suggested that HH1-1 had almost no toxicity both in vitro and in vivo . This adds new evidence to suggest that HH1-1 could be a promising therapeutic agent and support the pursuit of the Galectin-3 as a target in pancreatic cancer treatment.